SMART DECENTRALIZED SCHOOL - Phonprasert, Siripon (Journal of Educational Review Faculty of Education in MCU, 2025)
The advancement of digital technology in the 21st century has created both pressure and new opportunities for education systems worldwide. Modern schools can no longer function solely as traditional institutions for knowledge transmission; instead, they must transform into flexible learning spaces that utilize technology effectively. However, Thailand’s education administration remains centralized, which poses significant limitations, especially for small schools that require agility in decision-making. This article proposes the concept of the Smart Decentralized School, integrating modern technologies such as Artificial Intelligence (AI), dashboards, the Internet of Things (IoT), and Learning Management Systems (LMS) with participatory and decentralized leadership approaches. The analysis draws upon key conceptual frameworks including Smart Learning, Data-Driven Management, and Distributed Leadership. A comparative case study is presented between Saunalahti School in Finland, which has full autonomy to design its curriculum based on real-time data and policy support, and Wat Ban Lam Nang School in Phichit Province, Thailand—a small rural school that applies basic technologies and shared decision-making to manage and develop the school dynamically despite lacking full national policy backing. Both cases emphasize the importance of data, flexibility, and trust at the operational level. The article recommends that, to successfully implement Smart Decentralized Schools in Thailand, policy reforms are needed to devolve budgetary, academic, and data management authority to schools. Investments should be made in context-appropriate digital infrastructure, particularly for small schools, and human capacity must be developed to empower school leaders and teachers to utilize technology and data effectively. Furthermore, school collaboration networks should be fostered through Professional Learning Communities (PLCs) and central digital platforms to promote mutual learning and innovation. In conclusion, the Smart Decentralized School represents a strategic educational solution for the digital era, combining the power of technology with the leadership of teachers and local administrators to create a more intelligent, adaptive, and equitable education system in Thailand.